Germline pharmacogenomics as a tool to individualize therapy in breast cancer - Flockhart, David (Henry Stewart Talks, 2009)
Major clinical issues in the personalized treatment of breast cancer, The efficacy barrier: tamoxifen and anastrozole, Advances in targeting that have improved the treatment of breast cancer, Tumor-based expression arrays, Prognostic expression arrays remain valuable beyond tumor grade and stage, Pharmacogenetic principles, Principles for valuable predictive biomarkers, COBRA, Anti-estrogen therapy for breast cancer, The ELPH trial, Aromatase inhibitor side effects in the ELPH trial, The problem with aromatase inhibitors in Asia, Breast cancer around the world, Classic understanding of tamoxifen pharmacology, Tamoxifen metabolism, Endoxifen, Serum concentrations of tamoxifen and metabolites predict efficacy, CYP2D6, Relapse-free survival was worse in poor metabolizers, Clinical consequences, Pharmacodynamic pharmacogenomics, Multiple targets to inhibit angiogenesis, Bevacizumab in breast cancer: E2100 trial, Financial consequences of FDA decisions
Archived at 2021/02/25